The age of AI in healthcare research: An analysis of projects submitted between 2020 and 2024 to the Estonian committee on Bioethics and Human Research - Aive Pevkur; Kadi Lubi (Journal of Responsible Technology)
The ethical evaluation of healthcare research projects ensures the protection of the study participants’ rights. Concurrently, the use of big health data and AI analysis is rising. A critical question is whether existing measures, including ethics committees, can competently evaluate AI-involved health projects and foresee risks. Our research aimed to identify and describe the types of research projects submitted between January 2020 and April 2024 to the Estonian Council for Bioethics and Human Research (EBIN) and to analyse AI use cases in recent years. Notably, the committee was established before the significant rise in AI usage in health research. We conducted a quantitative and qualitative content analysis of submission documents using deductive and inductive approaches to gather information on the types of studies using AI and make some preliminary conclusions on readiness to evaluate projects. Results indicate that most applications come from universities, use diverse data sources in the research and the use of AI is rather uniform, and the applications do not exhibit diversity in the utilisation of AI capabilities.